Comparison of Self-regulation Components between the Disabled and Veteran Athletes and Non-athletes - B. Akbarzadeh; A. Esmailie; M. Dadashzadeh (Afarand Scholarly Publishing Institute, 2018)
Abstract Aims: Sports activity is of particular importance in improving the quality of life of the disabled individuals, and the enjoyment of sports activities results in the health of their body and soul as well as the improvement of their social relationships. The aim of this study was to compare the self-regulation components of disabled and veteran athletes and non-athletes. Instrument and Methods: This descriptive study was a causal-comparative research conducted in 2017 among all physical-motorized veterans and disabled athletes and non-athletes in Tabriz. A total of 151 subjects were selected, using purposeful sampling method. They were divided into two groups: athlete (78) and non-athlete (73). The instrument used in this research was Miller and Brownchr('39')s self-regulation scale. The data were analyzed by SPSS 22, using t-test and multivariate analysis of variance (MANOVA).  Findings: There was a significant difference between the athlete and non-athlete groups in the overall self-regulation and subcomponents such as acceptance, evaluation, launching, review, planning, implementation, and measurement, and in all of the components, the mean of the athlete group was higher compared with the non-athlete group (p=0.001). Conclusion: The level of self-regulation is higher in the disabled and veteran athletes compared with the disabled and veteran non-athletes.